How Charge, Size and Protein Corona Modulate the Specific Activity of Nanostructured Lipid Carriers (NLC) against Helicobacter pylori - Rute Chitas; Cláudia Nunes; Salette Reis; Paula Parreira; Maria Cristina L. Martins (MDPI AG, 2022)
The major risk factor associated with the development of gastric cancer is chronic infection with Helicobacter pylori. The available treatments, based on a cocktail of antibiotics, fail in up to 40% of patients and disrupt their gut microbiota. The potential of blank nanostructured lipid carriers (NLC) for H. pylori eradication was previously demonstrated by us. However, the effect of NLC charge, size and protein corona on H. pylori-specific bactericidal activity herein studied was unknown at that time. All developed NLC formulations proved bactericidal against H. pylori. Although cationic NLC had 10-fold higher bactericidal activity than anionic NLC, they lacked specificity, since Lactobacillus acidophilus was also affected. Anionic NLC achieved complete clearance in both H. pylori morphologies (rod- and coccoid-shape) by inducing alterations in bacteria membranes and the cytoplasm, as visualized by transmission electron microscopy (TEM). The presence of an NLC protein corona, composed of 93% albumin, was confirmed by mass spectrometry. This protein corona delayed the bactericidal activity of anionic NLC against H. pylori and hindered NLC activity against Escherichia coli. Overall, these results sustain the use of NLC as a promising antibiotic-free strategy targeting H. pylori.